Answer :

Given :

To prove :

Formula used : =


= - sinx

If u and v are functions of x,then = u + v

The CHAIN RULE states that the derivative of f(g(x)) is f’(g(x)).g’(x)

Given that y =

taking log on both sides

log y = log

log y = y log ()

Differentiating both sides with respect to x


= log() + y

= log() + y

= log() + y

log) = - y

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses